2012
DOI: 10.1128/aac.05658-11
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Antimicrobial Resistance and Serotypes of Streptococcus pneumoniae Isolates in Asian Countries: an Asian Network for Surveillance of Resistant Pathogens (ANSORP) Study

Abstract: Antimicrobial resistance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
219
11
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(265 citation statements)
references
References 25 publications
(39 reference statements)
29
219
11
6
Order By: Relevance
“…The similar results was reported by the ANSORP study in 2008-2009 that found low resistance rates to penicillin among pneumococcal isolates caused non-meningeal IPD (3.9%) but high resistance (57.5%) among meningeal isolates. 24 Therefore, penicillin should not be used as the empirical treatment in patients who may have meningeal involvement in this region. Resistance to fluoroquinolones was also low, 1.7%, 0.4%, 1.5%, and 13.4% for levofloxacin, moxifloxacin, gatifloxacin, and ciprofloxacin, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similar results was reported by the ANSORP study in 2008-2009 that found low resistance rates to penicillin among pneumococcal isolates caused non-meningeal IPD (3.9%) but high resistance (57.5%) among meningeal isolates. 24 Therefore, penicillin should not be used as the empirical treatment in patients who may have meningeal involvement in this region. Resistance to fluoroquinolones was also low, 1.7%, 0.4%, 1.5%, and 13.4% for levofloxacin, moxifloxacin, gatifloxacin, and ciprofloxacin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among serotype 19A in the ANSORP study, 86.0% showed erythromycin resistance. 24 This association was observed in a study in southern Israel before the introduction of PCV7 that found increased rate of penicillin and erythromycinnonsusceptible serotype 6A and 19A isolated in children with otitis media which was temporally associated with increased use of azithromycin and oral cephalosporins. 25 The clear benefits of PCV have led to the increased inclusion of PCV into the national immunization programs of many countries.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Although rate and pattern of antibiotic resistance vary according to geographic origin. Trend of antibiotic resistance rate did not seem to reduce in Asian countries, moreover most antibiotic-resistant streptococcal isolates were found to be resistant to more than one class of antibiotic [8]. These findings revealed high proportion of strains less susceptible to commonly prescribed drugs, especially beta-lactam, macrolide and tetracycline.…”
Section: Introductionmentioning
confidence: 93%
“…(Constenla, 2008). O uso de agentes antimicrobianos está entre as principais estratégias de combate as infecções pneumocócicas, porém a dificuldade em estabelecer um tratamento eficaz é devido ao surgimento de cepas resistentes a antibióticos, principalmente ß-lactâmicos (Kim et al, 2012;Moyo et al, 2012).…”
Section: Lista De Abreviaturas E Siglasunclassified